Pendidikan Inklusi dalam Perspektif Pendidikan Islam: Mewujudkan Keadilan dan Kesetaraan untuk Semua - Lestari, Ayu; Bahar, Herwina (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Inclusive education in the context of Islamic education is an important and relevant topic in efforts to create a fair and equitable education system for all individuals, including children with special needs. This research aims to describe, analyze, and provide a deep understanding of inclusive education in Islamic education. Using a qualitative method and a literature review approach, this research presents findings that demonstrate the importance of inclusion in creating education that embraces all children, amidst multicultural complexity. These findings have significant implications for inclusive education practices in Islamic schools and provide recommendations for future policies and practices. This research also offers suggestions for further research in this area, including more in-depth studies on effective inclusive education implementation strategies.